Melting of subducted sediments reconciles geophysical images of subduction zones - M. W. Förster (Nature Portfolio, 2021)
Here, the authors identify that magnetotelluric conductive anomalies commonly observed on the trenchward-side of volcanic arcs in subduction zones can be explained by subducted sediments. High-pressure experiments show that these sediment melts will react with the overlying mantle wedge to produce electrically conductive phlogopite pyroxenites.